PENGARUH RASIO AKTIVITAS DAN RASIO LEVERAGE TERHADAP TINGKAT PROFITABILITAS - Tri Noormuliyaningsih; Fifi Swandari (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
The objectives of this research to analyze the influence of activity ratio (inventory turnover, fixed assets turnover, and total assets turnover) and leverage ratio (debt ratio and debt to equity ratio) to profitability level (return on assets and return on equity) on food and beverage companies that listed in Indonesia Stock Exchange (IDX). Sample on this research consist of 14 (fourteen) food and beverage companies that listed in Indonesia Stock Exchange (IDX). The observation periods are 3 (three) years that start from 2012 until 2014. Multiple linear regression is a method that used to analyze data, and for testing the raised hypothesis with t test. The result of research conclude that debt ratio significantly affect the company’s profitability level (return on assets and return on equity) with value of negative coefficient. Other variables such as inventory turnover, fixed assets turnover, and total assets turnover are not affect to profitability level (return on assets and return on equity). Influence of debt to equity ratio an profitability level can not be concluded in this research